2018
DOI: 10.3390/v10040184
|View full text |Cite
|
Sign up to set email alerts
|

Arbidol (Umifenovir): A Broad-Spectrum Antiviral Drug That Inhibits Medically Important Arthropod-Borne Flaviviruses

Abstract: Arthropod-borne flaviviruses are human pathogens of global medical importance, against which no effective small molecule-based antiviral therapy has currently been reported. Arbidol (umifenovir) is a broad-spectrum antiviral compound approved in Russia and China for prophylaxis and treatment of influenza. This compound shows activities against numerous DNA and RNA viruses. The mode of action is based predominantly on impairment of critical steps in virus-cell interactions. Here we demonstrate that arbidol poss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 31 publications
3
65
0
1
Order By: Relevance
“…And while the trafficking inhibitor apilimod is well tolerated and a potent antagonist of EBOV and LASV (51,53,70; also this study), in an early test, it did not protect mice from lethal EBOV challenge (see reference 23), likely due to its inhibition of interleukin 12/23 (IL-12/23) production (reference 61 Among the fusion inhibitors tested, arbidol emerges as a candidate for future consideration, as it shows similar activities against LASV and EBOV and appears, in our assays, somewhat more potent against LASV-and EBOV GP-versus influenza HAmediated fusion and entry. Arbidol is approved and used in China and Russia against influenza and has shown strikingly broad antiviral activity (33,36,71). A single standard human dose (200 mg) of arbidol yields a C max lower (33,(72)(73)(74) than our preliminary indication ( Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…And while the trafficking inhibitor apilimod is well tolerated and a potent antagonist of EBOV and LASV (51,53,70; also this study), in an early test, it did not protect mice from lethal EBOV challenge (see reference 23), likely due to its inhibition of interleukin 12/23 (IL-12/23) production (reference 61 Among the fusion inhibitors tested, arbidol emerges as a candidate for future consideration, as it shows similar activities against LASV and EBOV and appears, in our assays, somewhat more potent against LASV-and EBOV GP-versus influenza HAmediated fusion and entry. Arbidol is approved and used in China and Russia against influenza and has shown strikingly broad antiviral activity (33,36,71). A single standard human dose (200 mg) of arbidol yields a C max lower (33,(72)(73)(74) than our preliminary indication ( Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Here we have identified several drugs with these attributes that show similar degrees of inhibition of LASV and EBOV entry. Moreover, three of them-amodiaquine, niclosamide, and arbidol-inhibit multiple enveloped viruses (33,36,57,60,71,(80)(81)(82)(83). Hence, a drug or drug cocktail containing these drugs could inhibit multiple enveloped viruses that enter cells through the endocytic pathway (49).…”
Section: Discussionmentioning
confidence: 99%
“…Arbidol (umifenovir) is a broad-spectrum antiviral compound approved in Russia and China for prophylaxis and treatment of influenza. This compound shows activities against numerous DNA and RNA viruses [27]. Arbidol was found to be effective to SARS-CoV-2 in vitro [28].…”
Section: Arbidolmentioning
confidence: 99%
“…However, neither neuraminidase inhibitor showed any effect on SARS-CoV. Arbidol, a broad-spectrum antiviral agent against several DNA and RNA viruses, has been approved in Russia and China for prevention and treatment of influenza [100]. Antiviral effect against Zika virus (ZIKV), West Nile virus (WNV) and tick-borne encephalitis virus (TBEV) has been demonstrated in Vero cells [100].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…Arbidol, a broad-spectrum antiviral agent against several DNA and RNA viruses, has been approved in Russia and China for prevention and treatment of influenza [100]. Antiviral effect against Zika virus (ZIKV), West Nile virus (WNV) and tick-borne encephalitis virus (TBEV) has been demonstrated in Vero cells [100]. Furthermore, it was shown that arbidol can inhibit six different isolates of ZIKV and can protect against the cytopathic effects of ZIKV [101].…”
Section: Therapeutic Agentsmentioning
confidence: 99%